Increasing cage complexity reduces abnormal behaviours in farmed blue foxes - Ojala, Eeva A.; Valros, Anna; Mononen, Jaakko (Elsevier, 2025)
We studied the long-term effects of biweekly rotated enrichment objects and a permanent shelter screen on abnormal behaviour, daily activity, and stress physiology in juvenile female blue foxes (aged 3–9 months). The experiment lasted seven months, from August to February, following a 2 × 2 factorial design with groups of 8–10 foxes. We compared extra enrichment (E) versus basic enrichment (B) and the presence of a shelter screen (S) versus no screen (N). In the final month, we analysed stereotypic and fur chewing behaviours in 38 blue foxes using 48-hour video recordings. Daily activity was measured through instantaneous sampling at 10-minute intervals (IS-10 min), while abnormal behaviours were monitored using IS-1 min during active periods. Faecal cortisol metabolite (FCM) concentrations were analysed from 24-hour faecal samples collected in January. Monthly weighing tracked bodyweight loss towards the spring and breeding season. Scrabbling (scratching/digging) and oral stereotypies were the most common categories of abnormal behaviour, with IS scores of 1.1–1.2 % during active periods. Foxes losing more than 10 % of their bodyweight were scrabbling more, though three individuals with high weight loss exhibited low scrabbling scores, indicating a non-linear association. Enrichment reduced oral stereotypies and inter-individual differences in activity rates. The shelter screen did not influence the occurrence of abnormal behaviours but might have a lowering impact on FCM concentrations. Only cage location had a clear impact on FCMs, whereas other effects might have been obscured by the high individual variation. Overall, our study suggests that providing enrichment objects and avoiding periods of excessive feed restriction can reduce abnormal behaviours in juvenile female blue foxes. Our results highlight the need for category-specific analysis in addition to examining total abnormal behaviours.
Keywords: abnormal repetitive behaviour; faecal cortisol metabolites; animal welfare; Vulpes lagopus; environmental enrichment